2011
DOI: 10.1182/blood-2010-08-301523
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation-induced shedding of platelet glycoprotein VI mediated by factor Xa

Abstract: This study evaluated shedding of the platelet collagen receptor, glycoprotein VI (GPVI) in human plasma. Collagen or other ligands induce metalloproteinasemediated GPVI ectodomain shedding, generating approximately 55-kDa soluble GPVI (sGPVI) and approximately 10-kDa platelet-associated fragments. In the absence of GPVI ligands, coagulation of platelet-rich plasma from healthy persons induced GPVI shedding, independent of added tissue factor, but inhibitable by metalloproteinase inhibitor, GM6001. Factor Xa (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 55 publications
5
65
0
Order By: Relevance
“…Once activated, GPVI is easily shed from the platelet surface by the extracellular proteases ADAM-10 and -17, which abolishes GPVI-induced responses (24). Interestingly, under clotting conditions this proteolytic cleavage appears to be regulated by FXa, but not by thrombin (4). This finding demonstrates a novel negative-feedback mechanism of the coagulation process on a platelet activation pathway.…”
Section: A Platelet Leucine-rich Repeat and Immunoglobulin Family Rementioning
confidence: 64%
“…Once activated, GPVI is easily shed from the platelet surface by the extracellular proteases ADAM-10 and -17, which abolishes GPVI-induced responses (24). Interestingly, under clotting conditions this proteolytic cleavage appears to be regulated by FXa, but not by thrombin (4). This finding demonstrates a novel negative-feedback mechanism of the coagulation process on a platelet activation pathway.…”
Section: A Platelet Leucine-rich Repeat and Immunoglobulin Family Rementioning
confidence: 64%
“…Recently, we have shown that active Factor X can promote ADAM10-mediated shedding of GPVI independent of platelet activation. 49 Shear may unfold GPVI into a conformer able to be cleaved by ADAM10, consistent with the "memory of shear" in which GPVI continues to be shed after the discontinuance of shear ( Figures 1E and 5) and the presence of only mature ADAM10 on platelets ( Figure 1G), an effect possibly elicited via shearinduced changes to actin and cytoskeletal networks, 50 which are directly linked to GPIb-IX-V and coassociated GPVI. 26 The finding that shear influences GPVI cleavage warrants further research into shear-dependent shedding of other ADAM substrates on platelets and other cell types in vivo.…”
Section: Shear-induced Shedding Of Gpvi 4317mentioning
confidence: 87%
“…Exposure to elevated shear or FXa induces shedding that is also independent of platelet activation. 62,63 Fibrin binds to multiple proteins on the platelet surface; 1 or more of these interactions may contribute to GPVI shedding, possibly by clustering and juxtaposing GPVI to ADAM10 and/or other metalloproteinases. Further, soluble fibrin can also reduce GPVI ligand-induced function in platelets, presumably by blockade or steric hindrance of the ligand binding site, as the effect was not blocked by GM6001.…”
Section: Discussionmentioning
confidence: 99%